2013
DOI: 10.7196/samj.6829
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer clinicopathological presentation, gravity and challenges in Eritrea, East Africa: Management practice in a resource-poor setting

Abstract: Most cases presented at younger age and advanced stage. These findings call for strengthening health education to promote early health-seeking behaviour and advocacy for the introduction of national screening, implementation of a management protocol and establishment of a radio-chemotherapy centre.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…Clinical and pathological factors will be discussed on the basis of articles from 7 African countries: Republic of South Africa (RSA) [24], Egypt [25,26,27], Nigeria [28], Eritrea [29], Morocco [30], Cameroon [31,32], and Rwanda [33]. …”
Section: Clinical and Pathological Presentation Of Bcmentioning
confidence: 99%
“…Clinical and pathological factors will be discussed on the basis of articles from 7 African countries: Republic of South Africa (RSA) [24], Egypt [25,26,27], Nigeria [28], Eritrea [29], Morocco [30], Cameroon [31,32], and Rwanda [33]. …”
Section: Clinical and Pathological Presentation Of Bcmentioning
confidence: 99%
“…16 Nevertheless, Iraq, categorized as a middle-income country by WHO/Eastern Mediterranean Regional Office, 17 documents far better prognostic indicators than those recorded in low-resource settings such as Eritrea in eastern Africa, where two-thirds of the cases are detected in advanced stages; the mean duration from the onset of symptoms to the time of seeking medical advice approaches 3 years. 18 …”
mentioning
confidence: 99%
“…16 In Eritrea, 80 of the 82 women who were observed received surgical intervention as their only treatment because there are no chemotherapy or radiotherapy options available nationally. 12 Nguefack et al 10 in Cameroon observed 42 women for breast cancer over a 3-year period, and nearly all were treated with some form of surgery (92.9%), despite the majority of patients presenting with stage III disease; 79% of patients received neoadjuvant chemotherapy to downstage tumors and therefore allow surgical excision and closure to occur. 10 This suggests a possible regional difference in approach to multidisciplinary breast cancer care, as well as a chasm in cultural attitudes toward surgical options, because very few women in Eritrea and Cameroon are refusing mastectomies in comparison with their counterparts in Nigeria.…”
Section: Surgerymentioning
confidence: 99%
“…6,8,15,17 Furthermore, the ability to assess surgical margins for tumor-free tissue is often not feasible, and postoperative follow-up is low. 12,16 …”
Section: Surgerymentioning
confidence: 99%
See 1 more Smart Citation